2019
DOI: 10.2135/cropsci2019.01.0009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Alleles at a Major Solid Stem QTL for Wheat Stem Sawfly Resistance and Agronomic Performance in Hexaploid Wheat

Abstract: Solid stems provide resistance to the wheat stem sawfly (WSS, Cephus cinctus Nort.) in wheat (Triticum aestivum L.). A major quantitative trait locus, designated Qss.msub‐3BL, controls most of the variation for stem solidness. Two alleles that differ for temporal expression of stem solidness have been identified. An allele derived from the cultivar ‘Rescue’, designated Qss.msub‐3BL.b, results in solid stems throughout stem development. An allele derived from the cultivar ‘Conan’, designated Qss.msub‐3BL.c, cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 42 publications
4
12
2
Order By: Relevance
“…Our results indicate that the use of the Conan‐derived allele for WSS resistance in winter wheat was not as effective as the Rescue‐derived Qss.msub‐3BL.b allele. These results contrast with the study of hard red spring wheat where the Conan‐derived allele provided similar levels of WSS resistance as the Rescue‐derived allele (Cook et al., 2019). We believe this is due to a greater number of adult WSS remaining active after the pith produced by the Conan‐derived allele is degraded in winter wheat.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Our results indicate that the use of the Conan‐derived allele for WSS resistance in winter wheat was not as effective as the Rescue‐derived Qss.msub‐3BL.b allele. These results contrast with the study of hard red spring wheat where the Conan‐derived allele provided similar levels of WSS resistance as the Rescue‐derived allele (Cook et al., 2019). We believe this is due to a greater number of adult WSS remaining active after the pith produced by the Conan‐derived allele is degraded in winter wheat.…”
Section: Discussioncontrasting
confidence: 96%
“…Temporal expression of the Qss.msub‐3BL.c solid stem phenotype in the Yellowstone NILs was significantly higher than NILs with the hollow stem Qss.msub‐3BL.a allele at early plant development and maturity growth stages (Figure 2). This is similar to what was observed in the hollow stem spring wheat genetic backgrounds (Cook et al., 2019; Varella et al., 2016). Additionally, stem solidness expressed by the Qss.msub‐3BL.c allele significantly declined between early and mature temporal solid stem measurements, which is also what was observed in spring wheat (Cook et al., 2019; Varella et al., 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, host plant resistance is of critical importance. Although host plant resistance that is due to the presence of solid pith in the stem can be relatively successful for reducing stem cutting in wheat ( Beres et al 2013 , Wu et al 2013 , Talbert et al 2014 , Carcamo et al 2016 , Varella et al 2016 , Adhikari et al 2018 ), solid stems may be compromised by environmental effects on pith expression ( Beres et al 2009 , 2017 ) and relative expression of the trait in different backgrounds ( Cook et al 2019 , Varella et al 2019 , Bainsla et al 2020 ). In addition to stem solidness, other defense-related metabolites, such as DIMBOA (2,4-dihydroxy-7-methoxy-1,4-benzoxazin-3-one), tricetin, and lignin are downregulated in C. cinctus -infested wheat stems when compared with uninfested stems ( Biyiklioglu et al 2018 ).…”
mentioning
confidence: 99%
“…The efficacy of WSS resistance is greatly influenced by both genotype (G) and growing environment, and (or) their interactions (GE) (Beres et al 2011). Genetic mapping confirmed that stem-solidness in wheat cultivars is controlled predominantly by the Qss.msub-3BL locus on chromosome 3B introduced from the Portuguese landrace (McNeal et al 1959;Varella et al 2019) and other minor genes located on chromosomes 3A, 3B, 3D, 5A, 5B, and 5D (Larson and MacDonald 1959;Cook et al 2004Cook et al , 2019Houshmand et al 2007;Nilsen et al 2017;Appels et al 2018;Varella et al 2019). The recently released hexaploid wheat reference genome reported a gene called SSt1 (Appels et al 2018), which is responsible for stem solidness controlled by the Qss.msub-3BL.b allele.…”
Section: Introductionmentioning
confidence: 94%